The tunnel seismic advance prediction method with wide illumination and a high signal‐to‐noise ratio. (12th August 2020) - Lu, Xinglin; Liao, Xian; Wang, Yao; Wang, Guimei; Fu, Zhihong; Tai, HengMing
ABSTRACT: Tunnel seismic prediction is widely used in the field of tunnel seismic advance detection. The illumination of the target and the signal‐to‐noise ratio of the data are two key factors affecting the precision of data interpretation. Current seismic prospecting has shortcomings on sites: (1) The lighting shots are solely towards one side of the tunnel wall, (2) the geophones are placed far away from the tunnel face and (3) the surface waves from the tunnel wall dominate over the reflection waves, lowering the signal‐to‐noise ratio of the data at the tunnel wall. This paper proposes a tunnel symmetrical geometry to tackle the above challenges. The arrangement is to place 12 sources uniformly on each side of the tunnel wall and six geophones on the tunnel wall and face. Results of simulated data and measured data show that the proposed method enables (1) broad illumination of the target body, (2) the enhancement of illumination energy of the target body, and (3) higher data signal‐to‐noise ratio. The proposed symmetrical geometry method provides better interpretation in terms of broader coverage, higher quality and greater distance of investigation.